2021
DOI: 10.3390/ijerph18158003
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready to Build Back “Healthier?” An Exploratory Analysis of U.S. State-Level Disaster Recovery Plans

Abstract: As communities recover from disasters, it is crucial to understand the extent to which states are prepared to support the recovery of health systems and services. This need has been emphasized by the United States’ experience with COVID-19. This study sought to assess public health activities in state disaster recovery implementation plans. In this exploratory, descriptive study, state-wide disaster recovery implementation plans were collected from emergency management agency websites and verified (n = 33). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Given the need for infrastructure changes, including increased green space, cool roofs, and updated building codes, to increase resilience against EHEs, recovery presents an opportunity to build both EHE and climate change resilience. However, a review of US state laws found that only 17 states have laws that explicitly assign public health agency responsibilities or authorities in disaster recovery (103); in addition, less than one-third of 33 assessed state-level disaster recovery plans explicitly mention health in the overall vision or goal of the plan nor are strategies outlined to address long-term health care or behavioral health needs (67). Accordingly, the health sector has a substantial opportunity to integrate more meaningfully into disaster recovery planning and preparedness, including by ensuring the linkage of disaster recovery plans with health improvement plans, climate action plans, and other long-term planning to create built environments that support health (59).…”
Section: Post-event Activities and After-action Reviewsmentioning
confidence: 99%
“…Given the need for infrastructure changes, including increased green space, cool roofs, and updated building codes, to increase resilience against EHEs, recovery presents an opportunity to build both EHE and climate change resilience. However, a review of US state laws found that only 17 states have laws that explicitly assign public health agency responsibilities or authorities in disaster recovery (103); in addition, less than one-third of 33 assessed state-level disaster recovery plans explicitly mention health in the overall vision or goal of the plan nor are strategies outlined to address long-term health care or behavioral health needs (67). Accordingly, the health sector has a substantial opportunity to integrate more meaningfully into disaster recovery planning and preparedness, including by ensuring the linkage of disaster recovery plans with health improvement plans, climate action plans, and other long-term planning to create built environments that support health (59).…”
Section: Post-event Activities and After-action Reviewsmentioning
confidence: 99%
“…Post-disaster data collection on damage and losses is critical for obtaining essential disaster information, particularly after events such as hurricanes, earthquakes, and tsunamis (5,6). An understanding of how governments can support the recovery of health systems and services in the aftermath of disasters is vital (7).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral health is not only critical in the planning phase for emergencies but also crucial for successful recovery strategies 1. Prior research on natural disasters and pandemics emphasizes the need to prioritize behavioral health in response efforts,2 which is applicable, given the current and ongoing COVID-19 response.…”
mentioning
confidence: 99%